Ascent : the rapid rise of rock climbing in Singapore - Chew, Jonathan Yu (Nanyang Technological University, 2021)
Once perceived as an extreme sport, rock climbing has gained popularity as a recreational and mainstream sport in Singapore. With the added boost from being included in the Tokyo Olympics, the local climbing scene is witnessing a wave of development spurred by the sport's growing prominence, passionate climbers and increased support from the nation's sports associations.